Procedural results and in‐hospital outcomes of percutaneous coronary intervention for chronic total occlusion in patients with reduced left ventricular ejection fraction: Sub‐analysis of the Japanese CTO‐PCI Expert Registry. Issue 1 (1st June 2022) - Kobayashi, Norihiro; Ito, Yoshiaki; Kishi, Koichi; Muramatsu, Toshiya; Okada, Hisayuki; Oikawa, Yuji; Kawasaki, Tomohiro; Yoshikawa, Ryohei; Tanaka, Hiroyuki; Katoh, Osamu
Abstract: Objectives: To evaluate the procedural results and in‐hospital outcomes of percutaneous coronary intervention (PCI) for chronic total occlusion (CTO) in patients with reduced left ventricular ejection fraction (LVEF). Background: While the technical success of general CTO‐PCI has improved, CTO‐PCI patients with reduced LVEF remain at high‐risk for adverse events. Methods: The data of 820 patients with LVEF ≤ 35% (Group 1), 1816 patients with LVEF = 35%–50% (Group 2), and 5503 patients with LVEF ≥ 50% (Group 3), registered in the Japanese CTO‐PCI Expert Registry from January 2014 to December 2019, were retrospectively analyzed. The primary endpoint was in‐hospital major adverse cardiac or cerebrovascular events (MACCEs), including death, myocardial infarction, stent thrombosis, stroke, and emergent revascularization. Secondary endpoints included procedural details, guidewire success, and technical success. Results: There were no differences in guidewire and technical success rates between the groups. In‐hospital MACCEs was significantly higher in Group 1 (Group 1 vs. Group 2 vs. Group 3: 3.4% vs. 1.7% vs. 1.5%,   p  = 0.001) and was especially driven by death (1.3% vs. 0.3% vs. 0.1%,   p  < 0.001) and stroke (0.7% vs. 0.2% vs. 0.2%,   p  = 0.007). Multivariate analysis showed that LVEF ≤ 35% (odds ratio [OR]; 1.58, 95% confidence interval [CI]; 1.04–2.41,   p  = 0.03) and New York Heart Association (NYHA) class ≥ 3 (OR; 2.01, 95% CI; 1.03−3.93,   p  = 0.04) were predictors of in‐hospital MACCEs. Conclusions: In‐hospital MACCEs were significantly higher in patients with LVEF ≤ 35%. LVEF ≤;35% and NYHA class ≥ 3 were predictors of in‐hospital MACCEs after CTO‐PCI.